2003
DOI: 10.1159/000068471
|View full text |Cite
|
Sign up to set email alerts
|

Papular Xanthoma Associated with Angiokeratoma of Fordyce: Considerations on the Nosography of This Rare Non-Langerhans Cell Histiocytoxanthomatosis

Abstract: Background: Papular xanthoma (PX) is a rare normolipidemic non-Langerhans cell histiocytoxanthomatosis affecting both children and adults. Objective: We describe an adult case of PX associated with angiokeratoma of Fordyce and review the literature in order to compare and discuss previous reports. Methods: We studied the clinical, histopathological, immunocytochemical and ultrastructural findings. Results: We report the findings of our case and compare our case with those described in the literature. Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…[2,3] Ultrastructural study reveals no Birbeck granules or laminated bodies. The results of both immunostaining and ultrastructural study indicate foamy cells of non-Langerhans histiocytic origin.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…[2,3] Ultrastructural study reveals no Birbeck granules or laminated bodies. The results of both immunostaining and ultrastructural study indicate foamy cells of non-Langerhans histiocytic origin.…”
Section: Discussionmentioning
confidence: 96%
“…[1] The diagnostic criteria in the literature include: (1) generalized asymptomatic yellowish papulonodular lesions that do not merge into plaques or involve flexural areas, (2) no visceral involvement, (3) normal lipid profile, (4) infiltrate of foamy cells with negative immunostaining for S-100 and CD1a, and (5) no primitive histiocytic phase or infiltrate of other inflammatory cells. [1,2] Initially, all cases of PX reported were adults and the lesions did not resolve spontaneously. In 1990, Caputo et al observed that the skin lesions in 10 children presented similar clinical and histopathologic features to those reported for adults, but with a self-healing course within 1-5 years, [3] where the healed lesions might leave transient hyperpigmentation and anetoderma-like scars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lesions of XD may require differentiation from those of Langerhans cell histiocytosis, juvenile xanthogranuloma, papular xanthoma, generalized eruptive histiocytosis, progressive nodular histiocytosis, multicentric reticulohistiocytosis, and eruptive xanthoma [26,27]. Differential diagnoses of XD are listed in table 2.…”
Section: Discussionmentioning
confidence: 99%